Realisasi Pembelajaran Pendidikan Islam dalam Sistem Pendidikan Nasional Pada Satuan Pendidikan Sekolah Dasar - Adisel, Adisel; Hazayimun, Halima; Robbyansa, Ilham; Prananosa, Ahmad Gawdy (JOEAI (Journal of Education and Instruction), 2022)
The purpose of this study was to determine the description of Islamic religious education learning in elementary school education units in terms of the implementation of the 2013 curriculum. This type of research is library research. The data collection of this research was taken from several sources, including; text books, curricula, books on the National Education Constitution, scientific journals, and other relevant sources. The results of the study, the role and position of Islamic religious education in the national education system are very flexible, but in fact the curriculum used today, namely the 2013 curriculum, places points that cannot be applied in the field in the learning process. In conclusion, the role and position of Islamic education in the national education system is flexible and important because it is a means of transportation to achieve educational goals, although in the 2013 curriculum there are several points that cannot be done in the learning process. Keywords: 2013 Curriculum, Islamic Education, Realization, Education System